Reinforced colour preference of parasitoid wasps in the presence of floral scent: a case study of a cross-modal effect - Soichi Kugimiya; Takeshi Shimoda; Junji Takabayashi (Animal Cognition)
Abstract We examined the possibility of a cross-modal effect in naïve Cotesia vestalis, a parasitoid wasp of diamondback moth larvae, by using artificial flower models of four colours (blue, green, yellow, and red) in the absence or presence of floral scent collected from Brassica rapa inflorescences. In a four-choice test, regardless of the floral scent, non-starved female wasps visited green and yellow models significantly more often than blue and red ones, although no significant difference was observed between visits to the green and yellow models. They seldom visited blue and red models. When starved, the wasps became even more particular, visiting yellow significantly more frequently than green models, irrespective of the presence of the floral scent, indicating that they preferred to use yellow visual cues in their food search. Furthermore, a factorial analysis of variance revealed a significant effect of the interaction between model colour and floral scent on the wasps’ visits to flower models. The floral scent induced starved and non-starved wasps to visit yellow and green models about twice as often as without the scent. A cross-modal effect of olfactory perception on the use of chromatic information by wasps may allow them to search efficiently for food sources.